1974
DOI: 10.1002/j.1551-8833.1974.tb02137.x
|View full text |Cite
|
Sign up to set email alerts
|

Virus Removal by Diatomaceous‐Earth Filtration–Part 2

Abstract: The removal of viruses from drinking‐water supplies is not a long‐established practice, but it is an issue of major concern. Diatorhaceous‐earth filtration has been demonstrated to remove viruses from water effectively; however, as this article emphasizes, more research of and experimentation with this process is necessary. Part 1, involving the study of the bacteriophage T2 for E. coli, appeared in JOURNAL AWWA, 66:2:98 (Feb. 1974).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Various approaches have been presented in the literature which have taken up this challenge: diatomaceous earth (DE) modified with polyelectrolytes, 5-7 DE modified with salts/hydroxides of aluminum, iron, magnesium and calcium, 5,6,8 fiberglass and cellulose modified with salts of Al, Fe, Mg and Ca, 9 fiberglass and cellulose modified with alumina-coated colloidal silica, 10 sand modified with Fe-and Al-hydroxide, 11 and granular anthracite and granular activated carbon coated with nanoporous Al 2 O 3 . 12 These and other studies of electropositive filter media 13,14 generally show that the strongest contribution to the adsorption process is made by electrostatic forces, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have been presented in the literature which have taken up this challenge: diatomaceous earth (DE) modified with polyelectrolytes, 5-7 DE modified with salts/hydroxides of aluminum, iron, magnesium and calcium, 5,6,8 fiberglass and cellulose modified with salts of Al, Fe, Mg and Ca, 9 fiberglass and cellulose modified with alumina-coated colloidal silica, 10 sand modified with Fe-and Al-hydroxide, 11 and granular anthracite and granular activated carbon coated with nanoporous Al 2 O 3 . 12 These and other studies of electropositive filter media 13,14 generally show that the strongest contribution to the adsorption process is made by electrostatic forces, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…An alternate approach is to modify the surface properties of the filter media, e.g., by coating with an electropositive material. The first investigators of this approach (Brown et al, 1974a, Brown et al, 1974bFarrah et al, 1988;Farrah et al, 1991) found that iron aluminum hydroxide coating increased removal of viruses by diatomaceous earth from less than 30% to greater than 80%. Subsequently, Lukasik et al (1996Lukasik et al ( , 1999) tested removal of viruses by columns filled with fine sand (less than 0.3 mm) coated with iron aluminum hydroxide.…”
Section: Introductionmentioning
confidence: 99%
“…Recently there has been considerable concern about virus diseases in drinking water (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). It has been suggested that a variety of pathogenic viruses, including the causative agents for such wellknown diseases as poliomyelitis and hepatitis, may be transferred via water.…”
Section: Viral Diseasementioning
confidence: 99%
“…Primary and secondary treatment removes 93 to 99%o of the bacteria (13) and 90 to 99.9Wo of the viruses (23) in domestic wastewater, but large concentrations of bacteria still remain. Physical-chemical treatment processes such as coagulation, filtration, and carbon adsorption remove various amounts of pathogens (15,18,23,26). Coagulation followed by settling or filtration has been shown to be one of the most effective means of virus removal; it is more effective than chlorination.…”
Section: Wastewater Disinfectionmentioning
confidence: 99%
See 1 more Smart Citation